Analisis Akuntabilitas, Transparansi dan Kepercayaan Terhadap Minat Membayar Zakat Pada Badan Amil Zakat Nasional Provinsi Sumatera Utara - solahuddin tanjung (Jurnal Ilmiah Ekonomi Islam, 2022)
This article discusses zakat, zakat is one part of worship of the pillars of Islam, zakat is legally obligatory to be paid if it has entered the criteria for being able to issue it and has reached the reckoning. The purpose of this study was to determine the effect of the variables of accountability, transparency and trust on interest. The research method use quantitative with multiple linear regression using SPSS. From the test results, the number of respondents in this study was 100 people. The findings in this study that accountability has an effect on interest, transparency has an effect on interest and trust has an effect on interest, simultaneously there is an influence between variables (accountability, transparency, trust) on interest. With a 95% confidence level or an error rate of 5%.